(untitled) (Jurnal Pustaka, 2026)
Dongdonan Salapan Wali Puhun is a living oral tradition within the Indigenous community of Kampung Adat Miduana, Balegede Village, Naringgul Subdistrict, Cianjur Regency. This tradition functions not only as a cultural narrative but also as a local knowledge system that integrates social ethics, cultural spirituality, and ecological awareness. This study aims to examine Dongdonan Salapan Wali Puhun as an oral tradition that contributes to the preservation of tatali paranti karuhun (ancestral customary norms) and serves as a mediating mechanism between the Indigenous community and their ancestors (karuhun). The research employs a qualitative approach using reflective ethnographic methods. Data were collected through in-depth interviews with kokolot adat (customary elders), participant observation, and documentation studies. The findings indicate that Dongdonan Salapan Wali Puhun encompasses ethical teachings, an ecological value system, and performative spiritual practices, including customary prayers, safety mantras, rajah, jangjawokan, singlar, and auspicious-day calculations. These practices fall under the authority of the nine Wali Puhun, who are understood as individuals selected through both genealogical lineage and spiritual legitimacy. These findings affirm that Dongdonan Salapan Wali Puhun functions as an oral spiritual archive and a system of cultural pedagogy that sustains harmonious relationships among humans, nature, and the ancestral dimension. This study contributes to the strengthening of scholarship on Sundanese oral traditions, Nusantara spirituality, and discourse on the protection of Indigenous communities grounded in local wisdom.